Marital Conflict Resolution and Influencing Factors (Studies on Married Women in Makassar) - Murdiana, Sitti; Agustiani, Hendriati (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
Despite the fact that conflict is an undeniable part in marriage life, yet it could be a serious threat for it. In addition, it may bring negative impact for an individual life, both personal and social life, particularly for the children involved in the marital conflict. This study aimed to determine the factors which influence marital conflict resolution. This study involved 107 married women as the respondents with specific age of 10-40 years old. The source of data was the questionnaire in the form of open-ended questions. It was classified based on the similarity of answer. The result showed that there were two primary factor groups which were evidenced to influence marital conflict resolution, namely internal and external factors. Internal factors consisted of emotion regulation, attachment, and trait. Meanwhile the external factors were the children and family factors.